Aerobic growth physiology of Saccharomyces cerevisiae on sucrose is strain-dependent - Soares Rodrigues, Carla Ines; Gombert, Andreas K.; Wahl, Sebastian Aljoscha (Fems Yeast Research, 2021)
Present knowledge on the quantitative aerobic physiology of the yeast Saccharomyces cerevisiae during growth on sucrose as sole carbon and energy source is limited to either adapted cells or to the model laboratory strain CEN.PK113-7D. To broaden our understanding of this matter and open novel opportunities for sucrose-based biotechnological processes, we characterized three strains, with distinct backgrounds, during aerobic batch bioreactor cultivations. Our results reveal that sucrose metabolism in S. cerevisiae is a strain-specific trait. Each strain displayed distinct extracellular hexose concentrations and invertase activity profiles. Especially, the inferior maximum specific growth rate (0.21 h-1) of the CEN.PK113-7D strain, with respect to that of strains UFMG-CM-Y259 (0.37 h-1) and JP1 (0.32 h-1), could be associated to its low invertase activity (0.04-0.09 U/mgDM). Moreover, comparative experiments with glucose or fructose alone, or in combination, suggest mixed mechanisms of sucrose utilization by the industrial strain JP1, and points out the remarkable ability of the wild isolate UFMG-CM-259 to grow faster on sucrose than on glucose in a well-controlled cultivation system. This work hints to a series of metabolic traits that can be exploited to increase sucrose catabolic rates and bioprocess efficiency.
CRIS-Team Scopus Importer:2022-01-11
Keywords: invertase; Saccharomyces cerevisiae; sucrose; yeast physiology